How to reduce processing times for site‐specific assessments from 29 to 5 days using a common‐sense approach: it does not have to be that hard. Issue 3 (27th March 2023) - Milosavljevic, Marianna; Hewitt, Lyndel; Fish, Janaye; Davis, Kimberley J.; McManus, Leah; Ashford, Bruce
Abstract: Researchers have reported limitations with research governance processes across Australia. This study aimed to streamline research governance processes across a local health district. Four basic principles were applied to remove non‐value‐adding and non‐risk‐mitigating processes. Average processing times were reduced from 29 to 5 days and end‐user satisfaction was improved, all within the same staffing levels.